THE IMAGE OF LAYLI AND RELATED FEMALE CHARACTERS IN ABDURAHMON JAMI AND ALISHER NAVOI’S “LAYLI AND MAJNUN” POEMS - Avezova, Aziza (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
Abdurahmon Jami and Alisher Navoi are masters of the word who enriched classical Eastern literature with unique and inimitable artistic images. In their works, all characters — from the main protagonists to episodic figures — possess individual traits and distinctive qualities. These images evoke a strong aesthetic response in readers and inspire repeated reading. In classical literature, the tradition of character creation often exhibits a certain degree of repetition. However, this repetition does not imply mere imitation; rather, it manifests through reinterpretation of existing images in new forms. Traditional artistic symbols are enriched with new meanings, aesthetic dimensions, and ideological interpretations within each era, author, and work. This tendency is particularly evident in the creative legacy of Abdurahmon Jami and Alisher Navoi. This article presents a comparative analysis of the image of Layli in Jami’s and Navoi’s “Layli and Majnun” epics. The study also examines the role of secondary female characters — such as Layli’s mother, nurse, and friends — in revealing Layli’s inner experiences and shaping her overall image.